PENGARUH GAYA KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN - Susiladewi Susiladewi; Basuki Basuki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The purpose of this study was to determine and analyze how much influencethe mutation, Job Promotion and competence either singly or jointly to the EmployeeCareer Development at the National Unity and Politics of North Barito regency.The design of this study using quantitative methods. Data were collectedthrough questionnaires to 40 respondents in the apparatus of National Unity and thePolitics of North Barito regency by using sampling techniques proportionate stratifiedrandom sampling to determine the respondents to each variable. Then analysis of thedata obtained in the form of quantitative analysis Quantitative Analysis of coveringvalidity and reliability, hypothesis testing through F test and t test and analysis test, thecoefficient of determination (R2). The data analysis technique used is the analysis ofmultiple linear regersi which serves to prove the hypothesis of the study.Results of the analysis found that the mutation variable (X1) of 40.2%,Promotions Position (X2) amounted to 63.8%, and Competence (X3) amounted to 84.2%singly or together have a positive and significant impact on Career DevelopmentEmployees (Y). Figures adjusted R-square of 0.892 indicates that 89.2% EmployeeCareer Development variables influenced by three independent variables used in theregression equation. While the remaining 10.8% is explained by other variables outsidethe three variables used in this study.